A comparison of faculty led, mentorship program and peer mentoring on nursing students wound dressing clinical skills. (June 2020) - Fard, Zeynab Rezaei; Azadi, Arman; Khorshidi, Ali; Mozafari, Mosayeb; O'Connor, Tom; Budri, Aglecia Moda Vitoriano; Moore, Zena; Patton, Declan
Abstract: Background: The promotion of clinical nursing education requires using modern educational methods to develop students' knowledge and skills. There are however many different models by which education can be delivered with a wealth of literature supporting varying approaches. This is of particular relevance to clinical education where to date no singular approach has been identified as being the most appropriate. Objectives: This study aimed to compare and investigate the effect of a peer education method, a mentor-led education method versus a traditional faculty-led method for instruction regarding surgical wound care skills among nursing students. Design: This study used an experimental three-group pre- and post-test design. Settings: The research was conducted within two surgical wards of a university-affiliated hospital in the west of Iran. Participants: A total of 102 nursing students (first and second year) were assigned to three groups; peer-led learning group (n = 34), mentorship-led group (n = 34) or a faculty-led control group (n = 34). Methods: To ascertain performance in surgical dressing skill, data was collected in each group before and after the respective educational intervention. Data was collected using a surgical dressing skills checklist made by the research team which was piloted prior to the study. All statistical analysis was performed using SPSS v.22.0 (SPSS Inc., Chicago, IL). Results: Based on findings, after the intervention, the mean (SD) scores of surgical dressing and wound care skills were 28.24 (4.63), 31.76 (4.89), and 29.12 (5.33) for the peer-led, mentor-led and faculty-led groups, respectively. There was no significant difference between mentor group and faculty group or between peer group and faculty group (P > 0.05). However, the findings did demonstrate statistical difference in performance in surgical dressings and wound care techniques in the mentorship group method compared to the peer method (P = 0.006). Conclusions: Although participants in the mentor group performed best of all groups, our findings demonstrate that those in the peer method group performed as well as those in the faculty-led group in surgical dressing performance. Therefore, it is recommended that peer and mentor learning methods are given consideration by curriculum planners in for use in the development of student nurse clinical skill and competence in surgical wound care.